Artificial Intelligence in the University Context. Contributions from Research (Revista Lusófona de Educação, 2025)
In recent years, Artificial Intelligence has been very present in our society and in educational discourses and practices in the university context. In this study, a mixed design was used to analyse the articles published in the last decade, available in Scopus, focusing on the contributions of AI to teaching methodologies in university teaching. A total of 129 articles were analysed, selected following the PRISMA method, from a bibliometric and content perspective. Indicators of productivity, collaboration, dissemination and impact were considered, as well as the three emerging categories: AI Uses, AI Methodologies and AI Perceptions. The concentration of papers focusing on the uses and evaluations made of AI in general or on tools, in particular, stands out. Among the most relevant conclusions, cybersecurity and cyberbullying stand out, both in the description of the dangers posed by these technologies, and among the advantages that their use in prevention may entail, or the possibilities for attention to diversity and educational inclusion. The studies highlight the lack of knowledge and preparation for their use in the university context and the need for updating and updated regulations. It is worth noting the lack of research that comprehensively analyses the specific methodologies used in AI-mediated classrooms. Finally, a series of recommendations are made for higher education teachers and students.